PROSES BERPIKIR KREATIF GURU DALAM MENDESAIN TUGAS MATEMATIK - Alam, Syamsu; Taufiq, Taufiq; Ramadhani, Widya Putri (Jurnal Pendidikan Matematika Unpatti, 2023)
Students have different backgrounds and abilities. Therefore, teachers must be good at choosing and giving math assignments to their students. The purpose of this study was to reveal the creative thinking process of teachers in designing math assignments. The participants in this study were elementary school teachers in Pangkep district, South Sulawesi based on their functional position (focusing on intermediate teachers). This study used a qualitative approach, with data collection methods using task-based interviews. From the results obtained, we found the subject's thinking process followed the sequence of stages of synthesizing ideas, constructing ideas, planning the application of ideas, and applying ideas.